2006
DOI: 10.1007/s00432-006-0080-1
|View full text |Cite
|
Sign up to set email alerts
|

TIS21 /BTG2/PC3 as a link between ageing and cancer: cell cycle regulator and endogenous cell death molecule

Abstract: TIS21/BTG2/PC3 , orthologs of mouse, human and rat, respectively, is initially identified as one of the early growth response genes and induced by various stimulations. TIS21 belongs to antiproliferative (APRO) gene family containing the BTG-Box A (Y 50 -N 71 ) and BTG-Box B (L 97 -E 115 ), which are highly conserved among various species. On the other hand, it has lately been found that the expression of TIS21 is constitutive and high in thymus, lung alveolar epithelium, proximal tubule of kidney and bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 64 publications
1
74
0
Order By: Relevance
“…These include several potential tumor suppressor genes including Bcl7a, Cyfip2, and Rgs2 (Zani et al, 1996;Jackson et al, 2007;Schwäble et al, 2005;van Doorn et al, 2005). Likewise, 25% of PAX5-induced genes were also downregulated in Stat5b-CA x Ebf1 +/ leukemias, including potential tumor suppressor genes or genes involved in suppressing cell proliferation such as Bach2, Btg1, Btg2, and Ucp2 (Table S3; Rouault et al, 1992Rouault et al, , 1996Sasaki et al, 2000;Lim, 2006;Baffy, 2010). Interestingly, in the case of PAX5- .…”
Section: Ar Ticlementioning
confidence: 99%
“…These include several potential tumor suppressor genes including Bcl7a, Cyfip2, and Rgs2 (Zani et al, 1996;Jackson et al, 2007;Schwäble et al, 2005;van Doorn et al, 2005). Likewise, 25% of PAX5-induced genes were also downregulated in Stat5b-CA x Ebf1 +/ leukemias, including potential tumor suppressor genes or genes involved in suppressing cell proliferation such as Bach2, Btg1, Btg2, and Ucp2 (Table S3; Rouault et al, 1992Rouault et al, , 1996Sasaki et al, 2000;Lim, 2006;Baffy, 2010). Interestingly, in the case of PAX5- .…”
Section: Ar Ticlementioning
confidence: 99%
“…Expression vectors of HA-Nur77, dominant-negative (DN)-Nur77, Hnf4-a, Pgc-1a, GR, and Flag-Btg2 were described previously (13,18,(20)(21)(22)(23). The small interfering RNAs for Btg2 were prepared as described previously (18).…”
Section: Construction Of Plasmids and Dnamentioning
confidence: 99%
“…It has been suggested that Btg proteins exert cellular functions by interacting with transcriptional coactivators or corepressors, hence modulating their transcriptional activities (Matsuda et al, 2001;Tirone, 2001;Duriez et al, 2004;Lim, 2006). For example, it has been found that Btg2 impairs G1-S cell cyclephase progression by inhibiting cyclin D1 transcription (Guardavaccaro et al, 2000), that it can associate with HoxB9 (Prevot et al, 2000), and BMPregulated Smad1 and 8 (Park et al, 2004) to promote their transcriptional activity, and that it can enhance Math1 promoter activity (Canzoniere et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Btg/ Tob genes are a newly characterized family of cell cycle modulators (Guehenneux et al, 1997). Studies in different model systems suggest that they act as antiproliferative genes, they can promote cell differentiation and also regulate apoptosis and cellular senescence (Matsuda et al, 2001;Tirone, 2001;Duriez et al, 2004;Lim, 2006). Btg/Tob genes encode for a group of structurally related proteins, characterized by the presence of two novel and highly conserved domains ("antiproliferative" boxes A and B) located in the first 120 residues of the protein (Guehenneux et al, 1997;Guardavaccaro et al, 2000).…”
Section: Introductionmentioning
confidence: 99%